Rancang Bangun Konverter Modbus RTU RS485 ke Modbus TCP/IP Berbasis ATMEGA2560 - Yusuf Sofyan; Sofy Fitriani (Journal of Computer System and Informatics (JoSYC), 2023)
In the electricity’s world, there are panels that are used to display electrical measurements or what is known as a Digital Panel Meter (DPM). This DPM measures physical quantities such as current, voltage, power, frequency and so on. In addition, this panel serves as a monitor for the quality of the electricity supply. In medium voltage systems, DPM is integrated with Automatic Meter Reading (AMR) which functions as a data collection tool for energy consumption of electricity consumers. So this DPM is a very important tool. Problems arise when connecting from one DPM to another, because this DPM usually uses RS-485 for its communication system. Such communication can only be carried out with equipment of the same standard. Therefore, it is proposed to design a Modbus RTU RS-485 converter to Modbus TCP/IP. This is done so that DPM communication can be directly connected to computers or to network devices such as routers, hubs and switches. Stages of research that begins with the analysis of problems and system requirements. Next do the design and realization. From the research conducted, the tool runs well. The test uses the modbus poll software as a comparison of the measurement results from the tool. The results show that the device data and those that appear on the modbus poll have high accuracy, for example, the device shows a voltage of 227.2 V; when using the software the result is 227.25 V